1995
DOI: 10.1073/pnas.92.4.1222
|View full text |Cite
|
Sign up to set email alerts
|

The structure of unliganded reverse transcriptase from the human immunodeficiency virus type 1.

Abstract: The crystal structure of the reverse transcriptase (RT) from the type 1 human immunodeficiency virus has been determined at 3.2-A resolution. Comparison with complexes between RT and the polymerase inhibitor Nevirapine [Kohlstaedt, L. A., Wang, J., Friedman, J. M., Rice, P. A. & Steitz, T. A. (1992) Science 256, 1783Science 256, -1790 and between RT and an oligonucleotide [Jacobo-Molina, A., Ding, J., Nanni, R., Clark, A. D., Lu, X., Tantillo, C., Williams, R. L., Kamer a heterodimer (p66/p5i), with domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
347
1
2

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(364 citation statements)
references
References 13 publications
10
347
1
2
Order By: Relevance
“…From the results obtained, we conclude that the ␤ and Pol subunits fulfill mainly a structural function similar to that of the p51 subunits of HIV-1 RT and EIAV RT (13,14,19,21,29,32). However, we cannot completely exclude the possibility that the large subunit fulfills some minor function in catalysis, since mutations in Asp 181 or Asp 505 of the ␤ subunit appear to have some impact on the polymerase or RNase H activities.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…From the results obtained, we conclude that the ␤ and Pol subunits fulfill mainly a structural function similar to that of the p51 subunits of HIV-1 RT and EIAV RT (13,14,19,21,29,32). However, we cannot completely exclude the possibility that the large subunit fulfills some minor function in catalysis, since mutations in Asp 181 or Asp 505 of the ␤ subunit appear to have some impact on the polymerase or RNase H activities.…”
Section: Discussionmentioning
confidence: 62%
“…amino acid residues of the polymerase and RNase H active sites of RTs are highly conserved (2,3,15). In addition, comparison of the crystal structures of HIV-1 RT and the finger and palm domains of murine leukemia virus RT indicates that the geometry of the polymerase active sites of RTs is highly conserved (6,14,19,29). We used this information for selecting the amino acids to be mutated in RSV RT to obtain enzymes impaired in their polymerase or RNase H activities.…”
Section: Mutagenesis Of Baculovirus Transfer Vectorsmentioning
confidence: 99%
“…4b) from the position that it occupies in DNA-bound HIV-1 RT complexes (51)(52)(53)(54)(55) and in unliganded HIV-1 RT structures crystallized in the absence of inhibitors (21,22,24). In other NNRTI complexes with HIV-1 RT, the displacement of Trp-229 is required for the rearrangements of Tyr-181 and Tyr-188 that occur upon inhibitor binding.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent structures of the enzyme with a number of different NNRTIs bound have demonstrated that these inhibitors bind to the same pocket, with only minor differences in protein conformation, and substantially overlap the site occupied by nevirapine (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Comparison of these structures with those of the apoenzyme shows that the NNRTI-binding pocket is induced upon NNRTI binding (21)(22)(23)(24).…”
mentioning
confidence: 99%
“…Stammers et al, 1990;Unge et al, 1990;Lloyd et al, 1991;Kohlstaedt et al, 1992;Jones et al, 1993;Jacobo-Molina et al, 1993;Stammers et al, 1994;Rodgers et al, 1995), although few showed diffraction to high resolution. The structure was eventually described [for RT in complex with the NNI nevirapine (Merluzzi et al, 1990)] based on data to a minimum Bragg spacing of 3.4 A (Kohlstaedt et al, 1992), and was later extended to 2.9 A resolution .…”
Section: Introductionmentioning
confidence: 99%